Urine Cytology in Patients with Long Standing Dialysis - Kattab, Yarub I; Al-Qazzaz, Mutaz A.; Mousa, Liqaa R (AL-Kindy College Medical Journal, 2007)
Background: Dialysis is in common use to treat patients with end stage renal failure .However longstanding dialysis harboring some cellular changes in various body fluids. This study was conducted in order to detect these changes in urine. Objective: The study was conducted to detect cellular changes in urine of patients with longstanding dialysis. Method: Fifty-three urine samples were examined cytologically obtained from patients with longstanding dialysis during 6 months period. Freshly voided midstream urine samples were taken . Samples were centrifuged and 2 to 3 drops of sediments were smeared on 2 glass slides and fixed in 95% ethyl alcohol then stained with Hand E stain to be evaluated. Results: Gross physical examination of all urine samples were neither purulent nor hemorrhagic .Microscopically there was increased exfoliation of urothelial cells except in 9 cases. No significant cytological atypia were seen in all urine samples. Excessive exfoliation in the absence of significant inflammation, hemorrhage and cytological atypia compared with control group. Conclusion: The study revealed that some cytological changes do occur in the urothelial cells of patients with longstanding dialysis. These changes need further attention and study to disclose their causes.